Visualization of protein interactions in living plant cells using bimolecular fluorescence complementation - Walter, Michael; Schumacher, Karin (The plant journal, 2004)
Dynamic networks of protein-protein interactions regulate numerous cellular processes and determine the ability to respond appropriately to environmental stimuli. However, the investigation of protein complex formation in living plant cells by methods such as fluorescence resonance energy transfer has remained experimentally difficult, time consuming and requires sophisticated technical equipment. Here, we report the implementation of a bimolecular fluorescence complementation (BiFC) technique for visualization of protein-protein interactions in plant cells. This approach relies on the formation of a fluorescent complex by two non-fluorescent fragments of the yellow fluorescent protein brought together by association of interacting proteins fused to these fragments (Hu et al., 2002). To enable BiFC analyses in plant cells, we generated different complementary sets of expression vectors, which enable protein interaction studies in transiently or stably transformed cells. These vectors were used to investigate and visualize homodimerization of the basic leucine zipper (bZIP) transcription factor bZIP63 and the zinc finger protein lesion simulating disease 1 (LSD1) from Arabidopsis as well as the dimer formation of the tobacco 14-3-3 protein T14-3c. The interaction analyses of these model proteins established the feasibility of BiFC analyses for efficient visualization of structurally distinct proteins in different cellular compartments. Our investigations revealed a remarkable signal fluorescence intensity of interacting protein complexes as well as a high reproducibility and technical simplicity of the method in different plant systems. Consequently, the BiFC approach should significantly facilitate the visualization of the subcellular sites of protein interactions under conditions that closely reflect the normal physiological environment.